Patricia McCormick’s Sold: A Narrative of Alerity and Savior - Sapkota, Binod (The Spectrum, 2025)
The article explicates Patricia McCormick's novel, Sold, for its portrayal of the issue of trafficking involving thirteen-year-old Laxmi. In the novel Lakshmi, a thirteen-year-old girl, tells her story from her life at foothills of mountain through the moments of Laxmi being a sexual slave to the moment of being rescued. Using the prominent concepts of literary representation, the analysis reveals that the author constructs a narrative of alterity—we and the other, first by exoticizing Nepali society, people and culture, then by constructing an aspirational psychology of the characters toward Western values. In that sense, the novel mobilizes new forms of cultural essentialism and reinforces a hierarchical perspective. The article concludes the need for a more responsible portrayal of human trafficking—one that recognizes local resilience and the global economic systems that enable exploitation. Sold could provide a more accurate and ethical representation of the issue by doing so.